Using an Adapted Case Study Approach to Understand Rural Veteran Experiences in Patient Engagement and Patient-Centered Care Research - Kara A. Zamora; Traci H. Abraham; Christopher J. Koenig; Coleen C. Hill; Jeffrey M. Pyne; Karen H. Seal (Qualitative Research in Medicine & Healthcare, 2020)
How to best engage rural veterans in mental health care is challenging and a topic of public health concern. Rural-dwelling veterans experience greater mental health burden and poorer outcomes than their urban counterparts, making rural veteran engagement in mental health care a public health concern. In this article, we describe how institutional notions of “patient engagement” align with or diverge from rural veteran patient experiences of engagement in mental health care. Using an adapted case study approach developed for our study, we detail the mental health care experiences of three rural-dwelling veteran participants. These case studies illustrate varied forms of mental health care engagement, including use of community resources and self-management activities, that might not be recognized by clinicians as contributing to mental health treatment. Our findings highlight how critical gaps in institutional definitions of care engagement fail to acknowledge veterans’ experiences.